Factors associated with physical inactivity among school-going adolescents: data from the Malaysian School-Based Nutrition Survey 2012 - Baharudin, Azli; Zainuddin, Ahmad Ali; Manickam, Mala A.; Ambak, Rashidah; Ahmad, Mohamad Hasnan; Mahadir Naidu, Balkish; Cheong, Siew Man; Chan, Ying Ying; Abu Saad, Hazizi; Ahmad, Noor Ani (Sage Publications, 2014)
The importance of physical activity to health is well recognized. Good health habits should begin from a young age. This article aims to explore physical activity among Malaysian school adolescents and factors associated with it. Data from the Malaysian School-Based Nutrition Survey (MSNS), comprising a nationally representative sample of school-going children aged 10 to 17 years, were used. The overall prevalence of physically inactive adolescents was 57.3%. Age in years (adjusted odds ratio = 1.2; 95% confidence interval = 1.16-1.23), gender - females (adjusted odds ratio = 2.9; 95% confidence interval = 2.66-3.10), afternoon school session, breakfast consumption (no breakfast and irregular breakfast), body mass index status (obese and underweight), and body weight perception (underweight perceivers) were significant factors associated with physical inactivity among Malaysian adolescents. Thus, there is evidence that programs to promote physical activity in this group should consider the combination of the aforementioned factors at the household, school, and community levels.